Atomic brain - Mascelli, Joseph V.; Russell, Vy, 1916-; Dwiggins, Sue, 1914-2011; Dillman, Dean, Jr., 1923-2004; Eaton, Marjorie; Gerstle, Frank, 1915-1970; Cinema Ventures; Cinetel Films ([Los Angeles, CA] : Cinema Ventures, 1963)
A wealthy, aging spinster finances a mad scientist's brain transplant experiments in the hope that she can be rejuvenated. They hire servant girls from Europe as guinea pigs, but their plans go awry and the plot is foiled. Much of the story is told with voice-over narration.
Originally released as a motion picture in 1963.
Marjorie Eaton, Frank Gerstle, Frank Fowler, Erika Peters, Judy Bamber, Lisa Lang and Xerxes the cat.
Cinematographer, Alfred Taylor; editor, Owen C. Gladden; music, Gene Kauer.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Brain -- Transplantation -- Drama; Scientists -- Drama; Science fiction films; Horror films; Feature films; Internet videos; Streaming video